2000
DOI: 10.1038/sj.cgt.7700267
|View full text |Cite
|
Sign up to set email alerts
|

Heat-directed gene targeting of adenoviral vectors to tumor cells

Abstract: Targeting therapeutic gene expression to tumor cells represents a major challenge for cancer gene therapy. The strong transcriptional response exhibited by heat shock genes, along with the beneficial therapeutic effects of hyperthermia have led us to develop a heatdirected gene -targeting strategy for cancer treatment. Heat shock gene expression is mediated in large part by the interaction of heat shock factor 1 with specific binding sites ( heat shock elements; HSE ) found in the promoters of heat -inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
(23 reference statements)
2
33
0
Order By: Relevance
“…15 Studies with the HSP promoter have shown in different studies that this promoter can permit induction rates of up to several hundred fold in response to hyperthermia in a range of 40 -45°C. 11,14 In contrast, our CAT-reporter assays revealed that the mdr1 promoter does not reach such heat-induction levels, indicating that further optimization of the promoter sequence maybe necessary to improve the heat-inducibility. In the light of the combined hyperthermia, chemotherapy and gene therapy, however, the observed increase of transgene expression might be 295 sufficient for improved tumor cell killing.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…15 Studies with the HSP promoter have shown in different studies that this promoter can permit induction rates of up to several hundred fold in response to hyperthermia in a range of 40 -45°C. 11,14 In contrast, our CAT-reporter assays revealed that the mdr1 promoter does not reach such heat-induction levels, indicating that further optimization of the promoter sequence maybe necessary to improve the heat-inducibility. In the light of the combined hyperthermia, chemotherapy and gene therapy, however, the observed increase of transgene expression might be 295 sufficient for improved tumor cell killing.…”
Section: Discussionmentioning
confidence: 82%
“…294 of these vector systems are based on the employment of the human heat shock protein 70 (HSP) promoter or of derivatives of this promoter to achieve heat-inducible gene expression at temperatures that are relevant for hyperthermic treatments of tumor patients. 11,13,14,29 In our study we were using a different human promoter, which is originally known to regulate the expression of the multidrug resistance gene mdr1. Because the mdr1 gene regulation responds to external stress stimuli such as UV irradiation, cytostatic drugs and also to hyperthermia, this promoter is an attractive candidate for the construction of hyperthermia-inducible vectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We 6 and others [7][8][9][10][11][12] have been working to harness hyperthermia as a modality to target therapeutic gene expression to tumor cells. Studies to date have demonstrated that hyperthermia shows significant promise as a way to achieve treatment-targeted, spatiotemporal control of gene expression in vitro 6,[8][9][10][11][12][13] and in vivo.…”
mentioning
confidence: 99%
“…Studies to date have demonstrated that hyperthermia shows significant promise as a way to achieve treatment-targeted, spatiotemporal control of gene expression in vitro 6,[8][9][10][11][12][13] and in vivo. 6,[8][9][10][11][12][13] LRBC is an excellent choice for the clinical application of heat-directed cancer gene therapy in that it is prevalent, responds to hyperthermia and is relatively uncomplicated in terms of treatment planning for heat dosimetry. It is also amenable to gene therapy because its superficial and localized nature renders it easily accessible for vector administration.…”
mentioning
confidence: 99%